When Information Isn’t Enough: Informative Isn’t Interactive in Food-Delivery App Advertising - Elfi Elfi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2025)
Food-delivery applications increasingly rely on social media advertising to communicate promotional content, yet the effectiveness of informative messages in driving user engagement remains unclear. This study explores how perceived informativeness in social-media–based advertising (SMAPI) shapes user responses in the food-delivery service setting in Indonesia. Food-delivery applications frequently rely on social platforms to communicate promotional content, yet it remains uncertain whether informative messages encourage engagement with brand-related content. Drawing on Advertising Value Theory, Source Credibility Theory, and the Value–Attitude–Behavior framework, this study examines the relationships among SMAPI, perceived ad credibility, evaluative attitudes toward the advertisement, and engagement with the brand. Data were collected through an online questionnaire using purposive sampling, involving 159 users of food-delivery applications who had recently encountered promotional content on social media. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) and a bootstrapping approach of 10,000 iterations. Results show that SMAPI positively influences ad credibility, which subsequently strengthens favorable attitudes toward the advertisement. Attitude toward the advertisement also significantly predicts engagement with the brand. However, the direct path from SMAPI to engagement outcomes and the serial mediation through credibility and attitude were not statistically significant. These findings suggest that while informational cues can shape cognitive and affective responses, they do not independently prompt interactive engagement. Practical implications emphasize the importance of incorporating emotional and participatory elements into promotional content to encourage deeper consumer involvement.